Ragam Metode Pembelajaran dalam Al-Qurian: Analisis Tarbawi dan Relevansinya bagi Pendidikan Islam Kontemporer - Fauziyah, Intan Nur; Mas'ud, Ali (Tarbawi : Jurnal Studi Pendidikan Islami, 2026)
Abstract Purpose – This article explores how the Qur’an conceptualizes learning methods and systematically categorizes them to support contemporary Islamic education, emphasizing dialogical, narrative, exemplary, and experiential approaches to enhance students’ critical, moral, and spiritual competencies. Design/methodology/approach - This research uses literature study and content analysis of tarbawi verses, classical and contemporary tafsir, as well as the latest literature to build a comprehensive framework for Al-Qur'an learning methods and analyze its implications for education. Research limitations/implications – The conceptual focus limits empirical testing; future research should explore applied classroom models or digital pedagogical innovations. Findings – Four major pedagogical categories are identified—dialogical, narrative, exemplary, and experiential—showing relevance for character formation, critical thinking, moral reasoning, and active learning. Qur’anic pedagogy is participatory, holistic, and humanistic, addressing limitations of teacher-centered approaches. Originality/value – The study provides an integrative framework linking classical Qur’anic insights with contemporary educational needs, offering a foundation for curriculum development and pedagogical innovation in Islamic education